Energy-related GHG Emissions for Inland and Municipal Economy in Chongqing: Factor Dynamics and Structure Decomposition. (December 2016) - Hu, Yi; Yin, Zhifeng; Ma, Jian; Du, Wencui; Liu, Danhe; Sun, Luxi
Abstract: As the largest and most populous city in China, Chongqing has a unique municipal economy structure and challenges in GHG emissions abetment that are greater than those of other cities. This paper quantifies sources of emissions growth in Chongqing using an IO-SDA framework. The twelve components studies are classified into three categories: change in intensities, production linkages, and final demand. The results show that the crucial factor of GHG emissions reduction is change of intensities, and the main cause of emissions growth is expansion of final demand.